Regulation of exogenous acyl homoserine lactones on sludge settling performance: Monitoring via ultrasonic time-domain reflectometry. (September 2022) - Dong, Deyuan; Liu, Qiuju; Wang, Xiaoyu; Hu, Haidong; Wu, Bing; Ren, Hongqiang; Wang, Jinfeng
Abstract: Despite extensive studies, a comprehensive solution for sludge bulking has not yet been found. This study improves the sludge settling performance via quorum sensing (QS) by adding exogenous acyl homoserine lactones (AHLs). First, a novel approach based on ultrasonic time-domain reflectometry, which can automatically and in-situ assess a sludge volume index (SVI), was developed using the displacement in the ultrasonic spectra as a feasible indicator (R 2 = 0.98, p < 0.01). Next, the effects of typical AHLs, i.e., 3OC6-HSL, C12-HSL, and 3OC14-HSL, on sludge settling properties were investigated. Results indicated that the three AHLs significantly promoted the sludge settleability by 1.90, 2.03, and 1.62 times, respectively. The regulation mechanisms were investigated from the perspective of sludge physicochemical properties and biological community interactions. The draining degree of water to extracellular polymeric substances (EPS) significantly increased ( p < 0.05) with all three AHLs. Meanwhile, the hydrophobic tryptophan content increased with the addition of 3OC6-HSL and C12-HSL. Hence, EPS hydrophobicity was promoted, which is conducive to microbial aggregation. In addition, molecular ecological networks of activated sludge (AS) indicated that bacterial community structures were more complex and species interactions were more intense when adding 3OC6-HSL and C12-HSL. Meanwhile, additional keystones were identified, with the proportion of QS species increasing by 63.6% and 22.2%, respectively. Exogenous 3OC6-HSL eventually decreased the gross relative abundance of filamentous bacteria by 2.37%. Overall, appropriate AHLs could enhance community stability and microbial cooperation by strengthening the communication hub role of QS species, thereby suppressing the overgrowth of filamentous bacteria and improving the sludge settleability. This study provides an effective strategy to determine the appropriate AHL to rapidly eliminate filamentous bulking problems. Graphical abstract: Image 1 Highlights: A novel approach to monitor the process of sludge settling was developed. Adding 3OC6-HSL, C12-HSL, and 3OC14-HSL significantly improved the sludge settleability. The extracellular polymeric substance hydrophobicity was promoted, improving sludge aggregation. The communication hub role of quorum sensing bacteria was strengthened.